PELATIHAN MANAJEMEN ORGANISASI PADA KARYAWAN RSIA HIKMAH SAWI - Enggal Sari Maduratna; Nailufar Firdaus (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2023)
RSIA Hikmah has a minimum number of human resources so there are several personnel with more than one workload. The division of workload is based on Presidential Regulation no. 77 of 2015 about guidelines for hospital organization. The community service team chose a theme on community service regarding Organizational Management Training due to incompatibility in the number of human resources with the needs of Hikmah Sawi RSIA management implementation. The methods used are pre test, post test and simulation with providing material about organizational management. Results of the post test scores on the average position overview item are 70, job description items are 50 and job requirements items are 50. While the post test scores after giving the material average on job overview items are 85, job description items are 80 and job requirements are 80. The difference of each item are job overview items 15, job descriptions 25 and job requirements 25. This shows a pretty good improvement on all three items, particularly on the simulation results of preparing organizational structure. Participants enthusiasm for the knowledge of preparing organizational structures and submitted job description is a basic requirement for the new organizational structure improvement, to be more effective in achieving the vision and mission of RSIA Hikmah Sawi.